The Role of Psychology in Da'wah - Junaidah Bt Mohamed (Universiti Sains Islam Malaysia, 2011)
This academic project was discussed about the role of psychology in Da'wah. This academic project is mean to know how far is the role of psychology in spreading Da'wah, this is because the societies today accepts easily the Islamic teaching persuasively rather than spreading it by force. Therefore, psychology is needed in spreading Da'wah. The methodology, which is used in this research, is library research. After all, the researcher realized that psychology is necessary in order to disseminate Da'wah. The Du'ats are also encouraged to use these approaches as ways to spread Da'wah. Hopefully, all of these approaches will benefit Du'at and helping them spreading Islamic Da'wah effectively.